Apakah Pengungkapan Dana CSR Memperkuat Nilai Perusahaan? Peran CSR Assurance sebagai Variable Moderasi - Eza Gusti Anugerah (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
This study explores the effect of corporate social responsibility (CSR) expenditure on firm value and examines the moderating role of CSR assurance in energy-sector companies listed on the Indonesian Stock Exchange from 2020 to 2022. Using purposive sampling, a total of 44 firms were analyzed over a three-year period. Panel data regression was employed, applying a random-effects model with cluster-robust standard errors, clustered at the firm level. The results reveal that CSR expenditure alone does not significantly influence firm value. CSR assurance exhibits a significant negative direct effect on firm value, while the interaction between CSR expenditure and CSR assurance shows a significant positive effect. These findings suggest that CSR assurance enhances the credibility of CSR expenditure, improving its impact on firm value. The study contributes to the literature by providing empirical evidence on the combined effects of CSR expenditure and assurance in energy-sector companies. Practically, it highlights the importance for firms to integrate third-party assurance into their CSR reporting to strengthen stakeholder trust and maximize value creation.